Urban residential greenness and adiposity: A cohort study in Stockholm County. (December 2018) - Persson, Å.; Pyko, A.; Lind, T.; Bellander, T.; Östenson, C.-G.; Pershagen, G.; Eriksson, C.; Lõhmus, M.
Abstract: Background: Increasing evidence suggests that exposure to residential greenness is associated with positive health outcomes among urban populations. However, few studies have considered effects on adiposity development in a longitudinal setting. Objectives: This study aimed to explore the association between long-term exposure to urban residential greenness and markers of adiposity. Methods: A cohort of 5126 adults from five municipalities in Stockholm County was examined clinically at baseline (1992–1998) and follow-up (2002–2006) after on average nine years. Time-weighted average exposure to urban greenness was estimated by Normalized Difference Vegetation Index (NDVI) within 100 m, 250 m, and 500 m buffers around the residential addresses of each participant. Multiple linear and Poisson regression models were used to estimate associations between greenness and change in weight and waist circumference as well as risk of overweight, obesity and central obesity. Co-exposures to air pollution, traffic noise and distance to water were also examined. Results: In women, higher levels of residential greenness were associated with a reduced increase in waist circumference during follow-up (β = −0.11 cm/year, 95% CI −0.14; −0.08 per one interquartile range increase in NDVI) and decreased risk for central obesity (IRR = 0.88: 95% CI 0.79; 0.99) in the 500 m buffer. No associations were observed for men or with regard to weight development or the risk of developing overweight or obesity. Exposure to low NDVI levels in combination with high NOx from road traffic and transportation noise as well as long distance to water rendered statistically significant increases in waist circumference in both sexes. Conclusion: Higher long-term exposure to greenness was associated with a reduced increase in waist circumference and lower risk of central adiposity in women but not in men. In both sexes, low NDVI exposure in combination with other environmental risk factors appeared particularly harmful. Highlights: Residential greenness is associated with a lower risk of central obesity in women. Combined air pollution, noise and low greenness exposure appear particularly harmful. Socio-economic factors and tobacco use were found to modify the association.